Protocol for establishing Youth and Women Quality Centres (YWQCs) - Bomuhangi, Allan; Yila, Jummai; Puskur, Ranjitha; Nchanji, Eileen (2025)
These are community-owned, community-led centres that facilitate and stimulate the adoption of technologies to support smallholder farmers in improving their production and productivity. The primary objective of the YWQCs is to help young people and women in farming strengthen their skills, access quality seeds and tools, and connect to markets, so they can grow their businesses and earn better incomes. The centres also connect smallholder farmers to extension services, input supplies, and markets to improve production, while advocating for value addition. The establishment of Youth and Women Quality Centres (YWQCs) can take several forms, each designed to meet the needs of different communities and ensure accessibility for farmers. The first type of YWQC is hosted by youth and women within a farmers’ cooperative society. In this setup, the cooperative typically provides essential resources, such as office space, basic infrastructure, and, in some cases, administrative support. This model leverages the existing cooperative structure, enabling members to access training, high-quality inputs, and market information in a familiar and trusted environment. The second type of YWQC is situated within government premises at the village or ward level. These centres benefit from government support, including physical space and, in some cases, funding or the facilitation of services. Being located on government property ensures a degree of legitimacy and oversight, while also making the centres accessible to a broader number of farmers within the local administrative area. Farmers can easily visit these centres to access quality inputs, receive guidance on best practices, and participate in training programs offered through public extension services. Finally, some YWQCs are privately hosted by smallholder farmers, either individually by a lead farmer or collectively. In this model, the hosts provide suitable space that is easily accessible to local farmers and can accommodate the activities of the YWQC. These privately hosted centres are often highly flexible, enabling hosts to tailor services to the specific needs of their communities. They may provide demonstrations of improved farming practices, facilitate access to high-quality seeds and tools, and serve as local points of aggregation and marketing for produce. Across all models, the key considerations for establishing YWQC include accessibility, functionality, and the capacity to support basic operations, such as training, input distribution, and advisory services. Each form of centre provides a platform for youth and women to actively participate in agricultural value chains, improve productivity, and strengthen their economic resilience.